Learning and Judgment Can Be Affected by Predisposed Fearfulness in Laying Hens - de Haas, Elske N.; Lee, Caroline; Rodenburg, T. Bas (Frontiers in Veterinary Science, 2017)
High fearfulness could disrupt learning and likely affects judgment in animals, especially when it is part of an animals’ personality, i.e., trait anxiety. Here, we tested whether high fearfulness affects discrimination learning and judgment bias (JB) in laying hens. Based on the response to an open field at 5 weeks of age, birds were categorized as fearful (FC) by showing no walking or vocalizing or non-fearful (NFC) by showing walking and vocalizing. At adult age, birds (n = 24) were trained in a go–go task to discriminate two cues (white or black) with a small or large reward. Birds that reached training criteria were exposed to three unrewarded ambiguous cues (25, 50, and 75% black) to assess JB. Task acquisition took longer for FC birds than for NFC birds, due to a left side bias, and more sessions were needed to unlearn this side bias. Changes in trial setup increased response latencies for FC birds but not for NFC birds. A larger number of FC birds than NFC birds chose optimistically in the last ambiguous trial (25% black). FC birds had a longer latency to choose in the ambiguous trial (75% black) compared to NFC birds. Prior choice in ambiguous trials and a preceding large or small trial affected latencies and choices for both types of birds. Our study showed that fearfulness was associated with differences in discrimination learning ability and JB. It appeared that FC birds used a rigid response strategy during early learning phases by choosing a specific side repeatedly irrespective of success. FC birds were more affected by changes in the setup of the trials in comparison to NFC birds. We speculate that FC birds are more sensitive to changes in environmental cues and reward expectancy. These factors could explain how high fearfulness affects learning.